If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -2y)(x + 2y) = 0 Multiply (2x + -2y) * (x + 2y) (2x * (x + 2y) + -2y * (x + 2y)) = 0 ((x * 2x + 2y * 2x) + -2y * (x + 2y)) = 0 Reorder the terms: ((4xy + 2x2) + -2y * (x + 2y)) = 0 ((4xy + 2x2) + -2y * (x + 2y)) = 0 (4xy + 2x2 + (x * -2y + 2y * -2y)) = 0 (4xy + 2x2 + (-2xy + -4y2)) = 0 Reorder the terms: (4xy + -2xy + 2x2 + -4y2) = 0 Combine like terms: 4xy + -2xy = 2xy (2xy + 2x2 + -4y2) = 0 Solving 2xy + 2x2 + -4y2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(xy + x2 + -2y2) = 0 Factor a trinomial. 2((x + -1y)(x + 2y)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(x + -1y)' equal to zero and attempt to solve: Simplifying x + -1y = 0 Solving x + -1y = 0 Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. x + -1y + y = 0 + y Combine like terms: -1y + y = 0 x + 0 = 0 + y x = 0 + y Remove the zero: x = y Simplifying x = ySubproblem 2
Set the factor '(x + 2y)' equal to zero and attempt to solve: Simplifying x + 2y = 0 Solving x + 2y = 0 Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 x + 0 = 0 + -2y x = 0 + -2y Remove the zero: x = -2y Simplifying x = -2ySolution
x = {y, -2y}
| 7x+8=9x-8 | | (y-tx)(8y-tx)= | | (x+y)(4x-5y)= | | 8x-3[5-(7-6x)]= | | (x+y^2)(x-5y^2)= | | (x-nu)*(9x+3nu)= | | (y+2bx^2)*(2y-3bx^2)= | | 6y-2x=-8 | | 4x-4+3x+12=6x+3 | | 3x+17+x+53=180 | | 5x^2-20x-160= | | h(t)=-16t^2+32t+14 | | 3x+19=11x-53 | | Iz+3z=11+9i | | 5a^2-a^3=0 | | 20=15-z | | 20=30-2 | | -7x+7=-14 | | 8(5-2x)=40 | | 2x-1=12x+36 | | 3x+7=2x-9 | | 2x^2-24x-26=0 | | (7+4a)=(5+2b) | | 2x-2+x+x+2=24 | | n/2-2n/16=3/4 | | (6+w)(5w+2)=0 | | x^4-2x^4-2x^3+2x-1=0 | | 4x-4+2x+8= | | (6x+5)= | | 8x+5(x+3)-8= | | 13x+13y=720 | | 14y=13(y+16) |